IMPLICATIONS OF QUALITY ON BUSINESS OF LOGISTIC COMPANIES - Stanojević, Darko D; Vasić, Miloš; Potkonjak, Aleksandra; Dimitrijević, Miloš (Journal of Applied Engineering Science, 2015)
In turbulent commerce which characterizes all its branches, quality represents one of the rare tools which for companies provide possibility for diversification and separation from (dis) loyalty competition. The exception, also, does not represent neither Lagermax AED and market of logistic services. Company - Lagermax AED, as a leader in Serbian market, have recognized world trends and starts with implementation of international ISO standards in own business. The aim of this paper is to indicate on some issues which company Lagermax have during the process of standards implementation, as well as all benefits which company have and will have in near future, which would be got from generally accepted and confirmed management system.